THE MOVEMENT OF ACTION RESEARCH IN EDUCATION: (Sharing problems, goals, and respect for teachers and students) - Siyaswati, Siyaswati (Buana Pendidikan, 2011)
Action research is concerned with diagnosing a problem in a specific context and attempting to solve it in that context: it is usually (though not inevitably collaborative - team of researcher and practitioners of work together on a project; it is participatory team members themselves take part directly or indirectly in implementing the research and it is self evaluative – modifications are continuously evaluated within the ongoing situation, the ultimate objective being to improve practice in some way or others.